Akta sejmikowe jako źródło do dziejów miast i mieszczaństwa - Bulińska, Kamila (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2022)
The paper discussed using dietine (sejmik) files in research on history of cities and bourgeoisie. Based on dietine files of Greater Poland provinces, the potential of utilizing this type of material during the exploration of the history of municipal centers in all regions of Poland were outlined. Additionally, the author created classification of the municipal issues debated on dietine sessions, encompassing seven principal categories
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne